2018
DOI: 10.3847/2041-8213/aaa967
|View full text |Cite
|
Sign up to set email alerts
|

The Progenitor Dependence of Core-collapse Supernovae from Three-dimensional Simulations with Progenitor Models of 12–40 M

Abstract: We present a first study of the progenitor star dependence of the three-dimensional (3D) neutrino mechanism of core-collapse supernovae. We employ full 3D general-relativistic multi-group neutrino radiation-hydrodynamics and simulate the postbounce evolutions of progenitors with zero-age main sequence masses of 12, 15, 20, 27, and 40 M e. All progenitors, with the exception of the 12 M e star, experience shock runaway by the end of their simulations. In most cases, a strongly asymmetric explosion will result. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 52 publications
8
128
1
Order By: Relevance
“…Simulating CCSNe with larger progenitor masses will also enable us to further study the relationship between compactness and explodability found in previous studies (O'Connor & Ott 2011). Intriguingly and in contrast to O'Connor & Ott (2011), a number of 3D neutrino-driven simulations (Chan et al 2018;Ott et al 2018;Kuroda et al 2018;Burrows et al 2020Burrows et al , 2019Walk et al 2019) observed shock expansion in some progenitors with rather massive and compact cores. From the point of view of gravitational-wave astronomy, high-mass progenitors are particularly interesting because they are expected to explode more energetically (Müller et al 2016a), which will result in stronger gravitational-wave emission (Müller 2017;Powell & Müller 2019;Radice et al 2019).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Simulating CCSNe with larger progenitor masses will also enable us to further study the relationship between compactness and explodability found in previous studies (O'Connor & Ott 2011). Intriguingly and in contrast to O'Connor & Ott (2011), a number of 3D neutrino-driven simulations (Chan et al 2018;Ott et al 2018;Kuroda et al 2018;Burrows et al 2020Burrows et al , 2019Walk et al 2019) observed shock expansion in some progenitors with rather massive and compact cores. From the point of view of gravitational-wave astronomy, high-mass progenitors are particularly interesting because they are expected to explode more energetically (Müller et al 2016a), which will result in stronger gravitational-wave emission (Müller 2017;Powell & Müller 2019;Radice et al 2019).…”
Section: Introductionmentioning
confidence: 90%
“…The fate of models m39 and y20 is reminiscent of other massive models in other recent works. (Ott et al 2018;Burrows et al 2020Burrows et al , 2019, in which the accretion shock radius expands continuously in the post-bounce phase and reaches large radii of 200 km and above early on. This suggests that such early shock revival as seen for m39 and y20 is plausible.…”
Section: Explosion Dynamicsmentioning
confidence: 99%
“…Our main parameter of interest is the resulting BH mass, which we estimate using the mass coordinate where the gravitational binding energy reaches 10 48 ergs. This allows for the possibility of mass loss during the final corecollapse from either a weak explosion (Ott et al 2018;Kuroda et al 2018), energy loss to neutrinos, or ejection of a fraction of the envelope caused by the latter (e.g., Nadezhin 1980;Lovegrove & Woosley 2013). This typically gives estimated BH masses within a few 0.01 M of the total baryonic mass slower than the escape velocity at the onset of core collapse.…”
Section: Methodsmentioning
confidence: 99%
“…Software: All figures presented in this paper were produced using Python, Matplotlib (Hunter 2007), NumPy (Oliphant 2006; van der Walt et al 2011), and SciPy (Jones et al 01 ).…”
Section: Acknowledgementsmentioning
confidence: 99%